Risk Factors for Venous Thrombotic Disease - Rosendaal, F.R. (Thrombosis and Haemostasis, 1999)
Venous thrombosis occurs in about 1 per 1,000 individuals per year.1,2 It usually affects the deep veins of the leg, but may occur in other sites, such as the upper extremities, cerebral sinus, liver and portal veins, or retinal veins. It also may occur in the superficial veins, usually in the leg. The predilection of thrombosis occurring in the leg is the result of the upright position of man, with the resulting slow antigravitational flow of blood in the veins of the leg. Embolization occurs when parts of the clot dislodge and are transported by the blood flow, usually through the heart to the vasculature of the lungs.3Thrombosis is a serious disorder. It may be fatal by pulmonary embolism, although this is rare (case fatality rate of venous thrombosis is estimated at 1% to 2%). A common, and often disabling, consequence of deep vein thrombosis is postthrombotic syndrome, with symptoms ranging from discoloration to pain and ulceration.4 Because thrombosis is not very rare and often has serious consequences, prophylactic treatment is focussed on preventing first events and recurrences through adequate knowledge about risks and risk factors.5